Development of Business Potential Through Promotion of Entrepreneurial Spirit Among University Students - Usman, Osly; Suparno, Suparno; Prihatni, Rida; Swaramarinda, Darma Rika; Lutfia, Annisa; Riswandi, Riswandi; Indriani, Susi; Indriyana, Saoki; Fauzi, Achmad (Jurnal KARINOV, 2024)
Perkembangan teknologi membawa transformasi dunia bisnis dan kewirausahaan. Menjadikan strategi sebagai elemen krusial untuk meraih profit, pertumbuhan, dan keberlanjutan usaha. Banyak startup baru bermunculan, tetapi tidak sedikit wirausaha baru mengalami kegagalan akibat kurangnya kemampuan membuat perencanaan dan penciptaan nilai produk. Untuk mengatasi tantangan ini, Business Model Canvas (BMC) muncul sebagai alat bisnis yang efektif. Workshop dan kompetisi BMC dirancang khusus untuk mengajarkan mahasiswa mengenai pentingnya kewirausahaan serta penerapan BMC secara praktis. Dalam workshop ini, mahasiswa diperkenalkan dengan elemen-elemen kunci BMC, baik dari aspek internal maupun eksternal. Melalui metode klasikal dan presentasi yang disampaikan oleh narasumber berpengalaman, peserta kegiatan diberikan berbagai perencanaan pengembangan bisnis berbasis digital, peluang, serta pengembangan dan tantangannya. Pada aspek akademik kegiatan pelatihan ini dipublikasikan dalam bentuk artikel ilmiah untuk memberikan informasi kepada masyarakat, serta berfungsi sebagai referensi berharga bagi pengembangan dalam pendidikan kewirausahaan Kata kunci— Business Model, Canvas, Indonesia, Kewirausahaan, Malaysia Abstract The development of Technology has transformed the world of business and entrepreneurship. Making strategy as a crucial element to achieve profit, growth, and sustainability. sustainability. Many new startups have emerged, but not a few new entrepreneurs fail due to lack of planning and value creation skills. and product value creation. To overcome this challenge, the Business Model Canvas (BMC) emerged as an effective business tool. Workshop and competition BMC workshops and competitions are specifically designed to teach students about the importance of entrepreneurship as well as the practical application of BMC. In this workshop, students are introduced to the key elements of BMC, both from internal and external aspects. Through classical methods and presentations delivered by experienced experienced resource persons, participants were given various plans for digital-based business development, opportunities, as well as development and challenges. challenges. In the academic aspect, this training activity was published in in the form of scientific articles to provide information to the community, as well as to serve as a valuable reference for development in entrepreneurship education. Keywords— Business Model, Canvas, Indonesia, Entrepreneurship, Malaysia